The effects of using video clips and images on reading comprehension of high school students : - Huỳnh, Đặng Bảo Trinh (Trường Đại học Cần Thơ, 2010)
The study aims at testing the effects of the implementation of the video clips and images to teaching and learning reading on learners' quality of EFL reading and investigating learners' attitudes towards the use of the video clips images in their reading class.